Multimedia communication enables innovators to coalesce and thrive: An experience among digital operators in Africa - Rambaldi, Giacomo (Technical Centre for Agricultural and Rural Cooperation, 2019)
To bring together and support a Community of Practice (CoP) around Unmanned Aerial Systems (UAS) in Africa, CTA established a WhatsApp thread to encourage digital interactions. This article explores how the platform has helped the community members access new business opportunities